2019
DOI: 10.1002/etc.4440
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Copper Added to Surface Water: Field, Laboratory, and Modeling Studies

Abstract: The fate and effects of copper in the environment are governed by a complex set of environmental processes that include binding to inorganic and organic ligands in water, soil, and sediments. In natural waters, these interactions can limit copper bioavailability and result in copper transport from the water column to the sediment. In the present study, data on the fate of copper added to lakes, microcosms, and mesocosms were compiled and analyzed to determine copper removal rates from the water column. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 43 publications
0
32
0
1
Order By: Relevance
“…Studies on Cu are particularly plentiful given the use of Cu sulfate as an algaecide in ponds, lakes, and reservoirs. In a recent review by Rader et al (), which included many of the references just cited, the time required for 70% removal of Cu varied from 0.84 to 27 d, with one exception of 130 d. For the majority of studies, >70% of the added Cu was removed from the water column within 16 d of dosing. For other metals, the referenced literature supports substantial metal removal on timescales of days to weeks.…”
Section: Approach Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on Cu are particularly plentiful given the use of Cu sulfate as an algaecide in ponds, lakes, and reservoirs. In a recent review by Rader et al (), which included many of the references just cited, the time required for 70% removal of Cu varied from 0.84 to 27 d, with one exception of 130 d. For the majority of studies, >70% of the added Cu was removed from the water column within 16 d of dosing. For other metals, the referenced literature supports substantial metal removal on timescales of days to weeks.…”
Section: Approach Results and Discussionmentioning
confidence: 99%
“…Studies on Cu are particularly plentiful given the use of Cu sulfate as an algaecide in ponds, lakes, and reservoirs. In a recent review by Rader et al (2019), which included many of the references just cited, the time required for Assessing removal of metals from the water column-Environmental Toxicology and Chemistry, 2019;38:1839-1849 literature supports substantial metal removal on timescales of days to weeks. For example, the mesocosm study of Diamond et al (1990b), which assessed the behavior of several metals in the same mesocosms, observed the following half-times (i.e., time at which concentration has decreased by 50%, average of the 2 mesocosms, in days): Co (4.35), Fe (10.8), Zn (17.6), As (19.2), Sn (9.45), Cs (22.65), and Hg (14.45).…”
Section: Intrinsic Properties Of Metal Ions In Aquatic Systemsmentioning
confidence: 99%
“…However, other studies report that although possible the release of metals from sediment is rather limited. Oxidation of anoxic sediments or resuspension events do not lead to the remobilisation of metals and rather indicate an irreversible transfer of metals from water to the sediment (Rader et al., 2019). However, resuspended metals strongly bound to particulate matter may be taken up by filter feeders and remobilised in the gastrointestinal tract (Weltens et al., 2000).…”
Section: The Frameworkmentioning
confidence: 99%
“…Diamond et al (1990) measured half‐times for metal radioisotope loss from the water column in lake enclosures. Rader et al (2019) evaluated loss of copper from the water column in laboratory and field experiments and in a unit world model. They concluded, for the majority of studies examined, that >70% of the added copper was removed from the water column within 16 d, hence meeting the criterion of 70% removal in 28 d. It has been shown that metal loss from the water column is principally by sorption to particles and settling.…”
Section: Comparison Of Properties For Polychlorinated Biphenyls (Pcbsmentioning
confidence: 99%